How do you find the zeroes of $f\left( x \right)={{x}^{2}}-5x-6$ by factoring?
Answer
Verified
442.2k+ views
Hint: We use both grouping method and vanishing method to solve the problem. We take common terms out to form the multiplied forms. Factorising a polynomial by grouping is to find the pairs which on taking their common divisor out, give the same remaining number. In the case of vanishing method, we use the value of $x$ which gives the polynomial value 0.
Complete step by step solution:
We apply the middle-term factoring or grouping to factorise the polynomial.
In case of ${{x}^{2}}-5x-6$, we break the middle term $-5x$ into two parts of $-6x$ and $x$.
So, ${{x}^{2}}-5x-6={{x}^{2}}-6x+x-6$. We have one condition to check if the grouping is possible or not. If we order the individual elements of the polynomial according to their power of variables, then the multiple of end terms will be equal to the multiple of middle terms.
Here multiplication for both cases gives $-6{{x}^{2}}$. The grouping will be done for ${{x}^{2}}-6x$ and $x-6$.
We try to take the common numbers out.
For ${{x}^{2}}-6x$, we take $x$ and get $x\left( x-6 \right)$.
For $x-6$, we take 1 and get $\left( x-6 \right)$.
The equation becomes ${{x}^{2}}-5x-6={{x}^{2}}-6x+x-6=x\left( x-6 \right)+\left( x-6 \right)$.
Both the terms have $\left( x-6 \right)$ in common. We take that term again and get
$\begin{align}
& {{x}^{2}}-5x-6 \\
& =x\left( x-6 \right)+\left( x-6 \right) \\
& =\left( x-6 \right)\left( x+1 \right) \\
\end{align}$
Therefore, $\left( x+1 \right)\left( x-6 \right)=0$ has multiplication of two polynomials giving a value of 0. This means at least one of them has to be 0.
So, values of x are $x=6,-1$.
We know for a general equation of quadratic $a{{x}^{2}}+bx+c=0$, the value of the roots of x will be $x=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$.
In the given equation we have ${{x}^{2}}-5x-6=0$. The values of a, b, c are $1,-5,-6$ respectively.
We put the values and get x as $x=\dfrac{-\left( -5 \right)\pm \sqrt{{{\left( -5 \right)}^{2}}-4\times 1\times \left( -6 \right)}}{2\times 1}=\dfrac{5\pm \sqrt{49}}{2}=\dfrac{5\pm 7}{2}=6,-1$.
Note: We find the value of x for which the function $f\left( x \right)={{x}^{2}}-5x-6$. We can see $f\left( 6 \right)={{6}^{2}}-5\times 6-6=36-30-6=0$. So, the root of the $f\left( x \right)={{x}^{2}}-5x-6$ will be the function $\left( x-6 \right)$. This means for $x=a$, if $f\left( a \right)=0$ then $\left( x-a \right)$ is a root of $f\left( x \right)$. We can also do the same process for $\left( x+1 \right)$.
Complete step by step solution:
We apply the middle-term factoring or grouping to factorise the polynomial.
In case of ${{x}^{2}}-5x-6$, we break the middle term $-5x$ into two parts of $-6x$ and $x$.
So, ${{x}^{2}}-5x-6={{x}^{2}}-6x+x-6$. We have one condition to check if the grouping is possible or not. If we order the individual elements of the polynomial according to their power of variables, then the multiple of end terms will be equal to the multiple of middle terms.
Here multiplication for both cases gives $-6{{x}^{2}}$. The grouping will be done for ${{x}^{2}}-6x$ and $x-6$.
We try to take the common numbers out.
For ${{x}^{2}}-6x$, we take $x$ and get $x\left( x-6 \right)$.
For $x-6$, we take 1 and get $\left( x-6 \right)$.
The equation becomes ${{x}^{2}}-5x-6={{x}^{2}}-6x+x-6=x\left( x-6 \right)+\left( x-6 \right)$.
Both the terms have $\left( x-6 \right)$ in common. We take that term again and get
$\begin{align}
& {{x}^{2}}-5x-6 \\
& =x\left( x-6 \right)+\left( x-6 \right) \\
& =\left( x-6 \right)\left( x+1 \right) \\
\end{align}$
Therefore, $\left( x+1 \right)\left( x-6 \right)=0$ has multiplication of two polynomials giving a value of 0. This means at least one of them has to be 0.
So, values of x are $x=6,-1$.
We know for a general equation of quadratic $a{{x}^{2}}+bx+c=0$, the value of the roots of x will be $x=\dfrac{-b\pm \sqrt{{{b}^{2}}-4ac}}{2a}$.
In the given equation we have ${{x}^{2}}-5x-6=0$. The values of a, b, c are $1,-5,-6$ respectively.
We put the values and get x as $x=\dfrac{-\left( -5 \right)\pm \sqrt{{{\left( -5 \right)}^{2}}-4\times 1\times \left( -6 \right)}}{2\times 1}=\dfrac{5\pm \sqrt{49}}{2}=\dfrac{5\pm 7}{2}=6,-1$.
Note: We find the value of x for which the function $f\left( x \right)={{x}^{2}}-5x-6$. We can see $f\left( 6 \right)={{6}^{2}}-5\times 6-6=36-30-6=0$. So, the root of the $f\left( x \right)={{x}^{2}}-5x-6$ will be the function $\left( x-6 \right)$. This means for $x=a$, if $f\left( a \right)=0$ then $\left( x-a \right)$ is a root of $f\left( x \right)$. We can also do the same process for $\left( x+1 \right)$.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE